Development of a β-TOF detector: An enhancement of the α-TOF detector for use with β-decaying nuclides. (16th March 2023) - Niwase, Toshitaka; Xian, Wenduo; Wada, Michiharu; Rosenbusch, Marco; Chen, Sidong; Takamine, Aiko; Liu, Jiajian; Iimura, Shun; Hou, Dongsheng; Yan, Shuxiong; Ishiyama, Hironobu; Miyatake, Hiroari; et al.
Abstract: Previously, we developed an α-TOF detector for correlated measurements of atomic masses and decay properties of radioactive isotopes using a multi-reflection time-of-flight mass spectrograph, and successfully demonstrated α-decay-correlated mass measurements of heavy and superheavy nuclides. In this work, we develop a β-TOF detector, an improvement upon the α-TOF detector, to extend this technology to β-decaying nuclides. Online commissioning with 81 Ga yielded a measured half-life of 1.44(31) s, in agreement with the previous literature, and confirmed the efficiency of detecting a decay-correlated event to be consistent with the solid angle limitation.